PERKEMBANGAN ASPEK SIKAP SOSIAL DAN ADAT ISTIADAT MASYARAKAT ADAT DAYAK MERATUS DI ERA REVOLUSI INDUSTRI 4.0 - Isra Ul Huda; Anthonius Junianto Karsudjono (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Attitude is an individual's attitude in acting which is the result of a stimulus received in his activities or experiences that can cause or influence the actions and behavior of the individual. Based on the background of the problem, the formulation of the research problem is how the development of aspects of social attitudes and customs of the Dayak Meratus in the era of the industrial revolution 4.0. The purpose of this study is to determine the development of aspects of social attitudes and customs of the Dayak Meratus in the era of the industrial revolution 4.0. The type of research used by the researcher is descriptive qualitative. According to Sugiyono (2016: 9) qualitative research methods are research methods used to examine the condition of natural objects where the researcher is the key instrument. Miles and Hubermen (1984), suggest that the activities in qualitative data analysis are carried out interactively and take place continuously until complete, so that the data is saturated. The size of the data saturation is indicated by the absence of new data or information. Activities in the analysis include data reduction (data reduction), data presentation (data display) and drawing conclusions and verification (conclusion drawing/verification). The results of the study show that honesty, discipline, a sense of responsibility, and tolerance and mutual cooperation are very important in the life of the Dayak Meratus indigenous people in the era of the industrial revolution 4.0. This is the foundation of life for the Meratus Dayak indigenous people, both in terms of natural management and social life. The customs and culture that have been inherited by the ancestors, the system of norms, customary law, customary rules and sanctions in customs are very important in the life of the Meratus Dayak indigenous people in the era of the industrial revolution 4.0. and preserving local wisdom by the younger generation is very important in the life of the Dayak Meratus indigenous people in the era of the industrial revolution 4.0. The conclusion in this study is that the aspect of social attitude consists of: honesty, responsibility, discipline, tolerance, and mutual cooperation, in the Industrial Revolution 4.0 Era for the Meratus Dayak community, assessing this is very important as the basis of daily life in responding to the flow of globalization for the people of Meratus. the younger generation in an increasingly advanced era. Aspects of Customs and Tradition consist of: culture, norms, customary law, and local wisdom, in the Industrial Revolution 4.0 Era for the Meratus Dayak Indigenous community, this is very important as law and norms to regulate the life of the Meratus Dayak Indigenous community.